Ossified Spinal Meningioma: A Case Report and a Review of the Literature - Taha, Mahmoud M.; Alawamry, Ahmed; Abdel-Aziz, Hesham R. (The Surgery Journal, 2019)
Ossified spinal meningiomas are a rare form of spinal tumors. These tumors increase surgical morbidities due to their hard consistency and strong adhesion to the neural tissue and relatively narrow surgical space. Here, the authors describe the clinical findings, surgical strategies, and histological findings of a patient with an ossified meningioma. Preoperative diagnosis of these tumors can prevent surgical morbidities. Total resection can be curative with the application of meticulous microsurgical techniques.
Keywords: ossified meningioma; spinal meningioma; intradural extramedullary